The features of national conscience formation of the students of Law Institute of National Aviation University - Сопілко, І. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article analyzes the approaches of understanding of the national conscience and the issues of standing andgrooving of the national conscience of the students of Law Institute. Also is explores the main principles of organizationof educational work in Law Institute of NAU, that promoting the formation of patriotic education of student youth.